PRODUKSI DAN UJI AKTIVITAS SELULASE DARI ISOLAT BAKTERI SELULOLITIK SUNGAI INDRAGIRI - Kiki Apriani; Yuli Haryani; Ganis Fia Kartika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cellulolytic bacteria has been isolated from water and sediment sample of Indragiri river waters. Cellulase was produced by cellulolytic bacterial isolates in 1% Carboxy Methyl Cellulose (CMC) liquid medium at 37°C, 150 rpm for 24 h. The specific activity of cellulase was determined by Nelson-Somogy’s method (cellulase enzyme activity) and Lowry’s method (protein concentration). 914-5 sedimen isolates showed the highest activity of the enzyme 12,246.10 -4 ± 0,5885.10 -4 U/mL from 17 other isolates that was significantly different at (P≤0,05) compared with the other isolate.